Pengaruh Game Online terhadap Motivasi Belajar Siswa SMA PGRI 1 Jombang - Wardani, Dian Kusuma; Amal, Muhammad Ichlasul (AS-SABIQUN, 2023)
Online games have become one of today's entertainment that is much loved by children, teenagers and even adults. With the rapid development of technology, there are more and more online games with various new features in them. This makes many people who spend a lot of time playing online games to the point of forgetting the time. The impact is that the time spent socializing and studying with their peers is relatively shorter. This is what makes their learning motivation reduced which makes their study time also decrease. This research was conducted to find out how much impact online games have for students on their learning motivation. This study uses quantitative methods to test several theories by examining the relationship between variables. To obtain data, the researchers used data collection techniques through the observation method, questionnaire method and literature study. The subjects of this study were 56 students at SMA PGRI 1 Jombang for the academic year 2022/2023 with details of 25 students in class XI IPS 3 and 31 students in class XI IPS 6. The analysis used in this study was a simple linear regression test. There are two prerequisites in analyzing data, namely validity and reliability tests, and normality and linearity tests. Based on the results of the tests performed, it can be concluded that the normality and linearity assumptions are met. Then a simple linear regression analysis can be performed. The interpretation of the simple linear regression model that is formed is that every increase in one unit of online game variables will reduce the learning motivation variable by 0.315